Listen to my heart life, love & Roxette - Fredriksson, Marie 1958-2019 (1984 Publishing, 2023)
"Listen to My Heart is a completely candid and passionate, heartbreaking yet often witty life story of one of rock music's most resilient lead singers, Marie Fredriksson from Roxette. Given only a few months to live following a harrowing diagnosis in 2002, Marie boldly forged ahead into a life with newfound courage and inspiration. She continued as both a solo singer and with Roxette, where she performed over 550 concerts, sold 75 million records, and released over 50 singles including several global hits. In all, Roxette is Sweden's biggest music group--second only to ABBA. Filled with behind-the-scenes stories involving everyone from Tina Turner and Elton John to The Rolling Stones and Frank Sinatra, Listen to My Heart also explores her humble family beginnings, an early tragedy in the sudden loss of Marie's sister, her transition into the music industry as a solo artist, and the formation and challenges of being in one of the world's most successful pop groups. All while trying to maintain a stable marriage and being a mother to two young children in the face of a life-altering illness. Marie passed away in the aftermath of her diagnosis in December, 2019. Heart-wrenching yet winning, and told with exceptional energy and sincerity, Listen to My Heart sheds new and revelatory light on the life and work of one of our generation's most talented and courageous artists. Contains a foreword by Marie's longtime friend, director Jonas Akerlund and over 100 personal photographs, live and backstage shots, and memorabilia images."--Amazon.com
Original Swedish version first published 2015 as: Kärleken till livet
Keywords: Fredriksson, Marie / 1958-2019; Roxette (Musical group); Rock musicians / Sweden / Biography; BIOGRAPHY & AUTOBIOGRAPHY / General; Rock musicians; Sweden; Autobiographies; Biographies; Biografie